Life-threatening hypernatraemic dehydration in breastfed babies. Issue 12 (11th May 2006) - Shroff, R; Hignett, R; Pierce, C; Marks, S; van't Hoff, W
Abstract : We describe five babies, who were exclusively breast fed, with life-threatening complications of hypernatraemic dehydration secondary to inadequate breast feeding. An increased awareness among health professionals is required so that this potentially devastating condition can be prevented.